Application of Statistic Quality Control Method and Kaizen Approach in Controlling the Quality of Potato Products - Haristanti, Sindy Nindia; Aprillya, Mala Rosa; Faizah, Mustika Ratnawati; Sulaiman , Yoga Aulia (Universitas Muhammadiyah Lamongan, 2025)
Abstract⎯ Quality control has the aim of reducing the number of defective or damaged products, maintaining products according to predetermined standards and avoiding the escape of defective products into the hands of consumers. Micro Enterprises play an important role in running a business to improve the economy by paying attention to product quality capital. One of the products that come from marine commodities is potato chips. This study aims to analyze the control of crab chips production whether the product is still within the control limits or not, as well as to find the cause of damage or defective products. To measure product damage that can be accepted by the company using the Statistical Quality Control (SQC) method which functions to manage and control the manufacturing process with statistical methods. The results of this study indicate that the control of the potato chips production process has been controlled because the points on the p map are still within the control limits, but there is still a need for improvement proposals to improve product quality by using the Kaizen 5W + 1H concept. Factors that cause damage are fishbone diagrams, materials, labor, methods and machines. Keywords⎯ Kaizen 5W + 1 H ; Statistical Quality Control